The Degenerating Substantia Nigra as a Susceptible Region for Gene Transfer-Mediated Inflammation. (15th May 2011) - Roca, Valeria; Casabona, Juan Cruz; Radice, Pablo; Murta, Verónica; Juan Pitossi, Fernando
Abstract : Parkinson's disease (PD) is characterized by the progressive degeneration of neurons in the substantia nigra pars compacta (SN). The naïve SN is highly susceptible to inflammation. In addition, microglial activation in the degenerating SN displays distinct characteristics that increase the reactivity of the region towards inflammatory stimuli. On the other hand, gene therapy for PD has recently move forward into clinical settings, with PD being the neurodegenerative disorder with the highest number of Phase I/II gene therapy clinical trials approved and completed. These clinical trials are not targeting the SN, but this region is a certain candidate for future gene therapy interventions. Here, the unique immune-related properties of the degenerating SN in the context of a putative gene therapy intervention are reviewed. Several variables affecting the host response to gene delivery such as vector type and dosage, age and stage of disease of patients, and method of gene delivery and transgene used are discussed. Finally, approaches to diminish the risk of immune-mediated toxicity by gene transfer in the SN are presented.